2005
DOI: 10.1007/s10265-004-0189-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechano-sensitive orientation of cortical microtubules during gravitropism in azuki bean epicotyls

Abstract: The orientation of cortical microtubules (cMT) during gravitropism was studied in epidermal cells of azuki epicotyls. The relative proportion of cells with longitudinal cMT increased in the upper epidermis, and those with transverse cMT increased in the lower epidermis. When epicotyls were kept straight during gravistimulation, no change in cMT orientation occurred in either the upper and lower epidermis. When epicotyls were forced to bend downward, cells with transverse cMT increased in the upper epidermis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 34 publications
1
19
1
Order By: Relevance
“…‘Pinot Noir’ was observed, which was already manifest at the lowest concentration (20 μM) tested. This Gd 3+ sensitivity is only slightly lower than the values found from patch–clamp measurements in onion scale epidermis (Ding and Pickard, 1993) and much higher than that reported for other plant tissues, such as adzuki bean hypocotyl (Ikushima and Shimmen, 2005). Interestingly, the alkalinization response in V. rupestris was much more reistant to Gd 3+ inhibition.…”
Section: Discussioncontrasting
confidence: 63%
“…‘Pinot Noir’ was observed, which was already manifest at the lowest concentration (20 μM) tested. This Gd 3+ sensitivity is only slightly lower than the values found from patch–clamp measurements in onion scale epidermis (Ding and Pickard, 1993) and much higher than that reported for other plant tissues, such as adzuki bean hypocotyl (Ikushima and Shimmen, 2005). Interestingly, the alkalinization response in V. rupestris was much more reistant to Gd 3+ inhibition.…”
Section: Discussioncontrasting
confidence: 63%
“…The study of molecular sensing mechanisms (2,15) can thus now be extended to the cross-talk between gravi-and propriosensing as a function of organ size. Candidate mechanisms for the proprioception of the curvature may involve mechanical strain-or stress-sensing (27,30) triggering microtubules reorientation (28,29). Ethylene seems to be involved (17) but not the lateral transport of auxin (21).…”
mentioning
confidence: 99%
“…For instance, Ikushima and Shimmen (2005) have recently shown in azuki bean epicotyls that the reorientation of cortical microtubules is controlled by curvature and not by gravity signals. The degree of contribution of microtubule reorientation to tropistic curvatures may be variable, according to species, organs, and culture conditions.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, it has been proposed that microtubule reorientation occurs as the result of tropistic curvature and is not the cause of the curvature (Fischer and Schopfer 1998). Recent analysis with azuki bean epicotyls also suggested that the reorientation of cortical microtubules was controlled by curvature and not by gravity signal (Ikushima and Shimmen 2005). However, in maize coleoptiles, microtubules do not reorient passively after curvature, but reorient actively in response to gravitropic stimulation (Himmelspach and Nick 2001).…”
Section: Introductionmentioning
confidence: 92%